Pelatihan Pembuatan Ice Cream Talas untuk Meningkatkan Pemanfaatan Potensi Kekayaan Lokal di Desa Todanan Blora - Nur'aini, Siti; Purnawanto, Ahmad Teguh; Sholikah, Dwi Nafiatun Nisaus; Puspitasari, Titik (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This community service aims to increase the utilization of the village's local wealth potential and empower PKK cadres in Todanan Village, Blora Regency. Taro is one of the superior agricultural products in Todanan village that has not been optimally utilized as a processed product with high economic value. With this training, PKK cadres are expected to have knowledge and practical skills in processing taro into healthy, attractive, and valuable ice cream. The research method used is descriptive qualitative method with a participatory approach, involving observation, interviews, and documentation during the training activities. The PKM results show that this training not only improves the skills of PKK cadres in processing local agricultural products, but also fosters entrepreneurial motivation and opens up opportunities for micro-business development based on village potential. It is hoped that this training can make a positive contribution to improving the family economy and preserving local food and growing the micro economy in Todanan village, Blora Regency.